2016
DOI: 10.1515/pjct-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Ni(II), Pb(II) and Zn(II) on calcium alginate beads: equilibrium, kinetic and mechanism studies

Abstract: The biosorption process of three divalent metal ions -nickel, lead and zinc-from on calcium alginate from aqueous solution was studied, in single component systems. The biosorbent were investigated by Fourier Transform Infrared Spectroscopy. The batch mode experiments of the adsorption process were carried out as a function of pH, initial metal ions concentration, sorbent dosage and contact time. The adsorption infl uencing parameters for the maximum removal of metal ions were optimized. The experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 15 publications
(4 reference statements)
4
43
0
2
Order By: Relevance
“…The values of the current study were below the values for adsorption of Ni 2+ by alginate beads reported in the literature. The values for Cd 2+ range from 10.20 mg/g obtained by Mahmood, Z. et al [38] to 198.43 mg/g obtained by Papageorgiou, S.K. (Sips model) [15].…”
Section: Analysis Of Adsorption Isothermsmentioning
confidence: 86%
“…The values of the current study were below the values for adsorption of Ni 2+ by alginate beads reported in the literature. The values for Cd 2+ range from 10.20 mg/g obtained by Mahmood, Z. et al [38] to 198.43 mg/g obtained by Papageorgiou, S.K. (Sips model) [15].…”
Section: Analysis Of Adsorption Isothermsmentioning
confidence: 86%
“…The absorbance in the range 3000 to 3500 cm −1 , characteristic for the stretching of hydroxyl bonds (O-H), was the highest for samples crosslinked with calcium ions. Tensile vibration bands of symmetrical and asymmetrical CO carboxyl bonds and divalent ions were observed at values ranging from 1400 to 1600 cm −1 , while bands from 1000 to 1200 cm −1 characteristic for C-O bond vibration, at 800 cm −1 characteristic for mannuronic acid, and at 700 cm −1 characteristic for guluronic acid were also observed upon binding crosslinking ions [32][33].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir-atr)mentioning
confidence: 98%
“…Prvi linearni deo zavisnosti može se pripisati brzoj površinskoj adsorpciji, drugi -intračestičnoj difuziji, dok poslednji linearni deo zavisnosti pretstavlja finalni ravnotežni stupanj. S obzirom da su prikazane zavisnosti multi-linearne, i obzirom da ne prolaze kroz koordinatni početak, može se zaključiti da intračestična difuzija utiče na brzinu, ali nije jedini stupanj koji kontroliše brzinu adsorpcije [22,23,28]. Intračestična difuzija je nešto brža kod adsorpcije na modifikovanim vlaknima konoplje, usled lakše penetracije jona metala kroz fibrilisanu strukturu, mikropore i mikropukotine, do aktivnih mesta za adsorpciju.…”
Section: Tabela 3 Adsorpcioni Kapaciteti Uzoraka K I Ak Dobijeni Eksunclassified
“…Trake na 1602,7 i 1419,7 cm -1 , koje su posledica simetričnih i asimetričnih vibracija istezanja karboksilatnog anjona, COOH grupe, posle adsorpcije metalnih jona gotovo isčezavaju, što ukazuje da ove grupe gotovo u potpunosti učestvuju u jonskoj izmeni i kompleksaciji jona. Ovim se može podržati pretpostavka da je mali udeo alginata u kompozitu razlog manjeg sorpcionog kapaciteta kompozita u odnosu na čist alginat [17,28], jer je alginat nosilac karboksilnih grupa za koje se vezuju joni metala. U cilju poboljšanja efikasnosti ovog biosorbenta, potrebno je izvršiti optimizaciju količine alginata koji se koristi za impregnaciju vlakana konoplje.…”
Section: Tabela 3 Adsorpcioni Kapaciteti Uzoraka K I Ak Dobijeni Eksunclassified